Multi-band accelerated spin-echo echo planar imaging with reduced peak RF power using time-shifted RF pulses - Auerbach, Edward J. (2013)
PURPOSE: To evaluate an alternative method for generating multi-banded RF pulses for use in multiband slice-accelerated imaging with slice-GRAPPA unaliasing, substantially reducing the required peak power without bandwidth compromises. This allows much higher accelerations for spin-echo methods such as SE-fMRI and diffusion-weighted MRI where multi-banded slice acceleration has been limited by available peak power. THEORY AND METHODS: Multi-banded “time-shifted” RF pulses were generated by inserting temporal shifts between the applications of RF energy for individual bands, avoiding worst-case constructive interferences. Slice profiles and images in phantoms and human subjects were acquired at 3T. RESULTS: For typical sinc pulses, time-shifted multi-banded RF pulses were generated with little increase in required peak power compared to single-banded pulses. Slice profile quality was improved by allowing for higher pulse bandwidths, and image quality was improved by allowing for optimum flip angles to be achieved. CONCLUSION: A simple approach has been demonstrated that significantly alleviates the restrictions imposed on achievable slice acceleration factors in multiband spin-echo imaging due to the power requirements of multi-banded RF pulses. This solution will allow for increased accelerations in diffusion-weighted MRI applications where data acquisition times are normally very long and the ability to accelerate is extremely valuable.